Cyber Media and Diversity Issues in Indonesia - Harry Susanto, Eko; Loisa, Riris; Junaidi, Ahmad (Estudios sobre el Mensaje Periodístico, 2020)
Cyber media research in its relation to diversity is part of mass communication study particularly cyber media journalism which emerges fast nowadays. In the framework of political democracy in Indonesia, coverage and news coverage on diversity issues depend on the characteristics of the cyber media. Therefore, it is possible that the information being received can differ from one to another cyber media. Since cyber media have speed of information dissemination, they should be able to disseminate messages in accordance with the essential and importance of diversity. This does not disregard definitely that information from cyber media become reference for public to behave and take actions. This study aims to describing the meaning of cyber news coverage, describing cyber news coverage from the aspect of newsworthiness, reviewing the use of news coverage information, and analyzing various news coverage topics in cyber media. As the result, this study found the number of words related to cyber media attention to diversity issues, cyber news coverage that puts forward verification and newsorthiness, and different news coverage topics of diversity issues in each cyber media.